2020
DOI: 10.1016/j.buildenv.2019.106478
|View full text |Cite
|
Sign up to set email alerts
|

Lighting for work: A study of the relationships among discomfort glare, physiological responses and visual performance

Abstract: Objective measures of visual discomfort have the potential to quantify the individual's sensations under discomfort glare conditions although such measures have yet to be circumscribed. The present study aimed to examine the extent to which visual discomfort sensation can be both operationalised and measured, utilising many light-induced physiological measures. These measurements were coupled with visual performance evaluations, in combination with conventional measures of photometric measurements and subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 54 publications
1
24
0
4
Order By: Relevance
“…Lee et al [43] and Hamedani et al [44] conducted experiments in an office involving a reading task, testing whether people were able to read a text printed in 12-point Times New Roman font on an A4-sized (210 × 297 mm) sheet of paper under a given illumination environment. In our study, a reading task was issued using a text in 12-point Ba-tangChe font on an A4-sized sheet of paper.…”
Section: Reading Taskmentioning
confidence: 99%
“…Lee et al [43] and Hamedani et al [44] conducted experiments in an office involving a reading task, testing whether people were able to read a text printed in 12-point Times New Roman font on an A4-sized (210 × 297 mm) sheet of paper under a given illumination environment. In our study, a reading task was issued using a text in 12-point Ba-tangChe font on an A4-sized sheet of paper.…”
Section: Reading Taskmentioning
confidence: 99%
“…At the same time, it contributes to decreasing the need for electrical lighting, one of the primary sources of energy costs in offices with deep spaces [6,7], while contributing to improving the building's overall sustainable performance. A substantial number of studies investigating daylighting in buildings showed that lighting environments play an essential role in occupant satisfaction towards visual comfort and overall indoor environmental quality [8,9]. Glare is one relevant component defining the perceived lighting quality.…”
Section: Introductionmentioning
confidence: 99%
“…As principais causas de desconforto são geralmente relacionadas à incapacidade de o sistema visual se adaptar às condições dinâmicas e direcionais do brilho dos componentes da cena, podendo gerar diferentes padrões comportamentais (WIENOLD;CHRISTOFFERSEN, 2006), os quais são difíceis de ser definidos. As reações do sistema visual às condições de iluminação têm sido alvo de estudos que propõem modelos para a inclusão das sensações visuais nos índices usados na avaliação do ofuscamento (CHOI;ZHU, 2015;HAMEDANI et al, 2019HAMEDANI et al, , 2020HOWARTH et al, 1993;STONE, 2009;SWEITZER;SAITO, 1995;YAMIN GARRETÓN et al, 2015). Em um estudo inicial, Howarth et al (1993) não encontraram relação entre a variação no tamanho da pupila e a sensação de desconforto; porém, estudos posteriores afirmaram que a dita variação é sim um indicador de conforto visual (CHOI;ZHU, 2015;SWEITZER;SAITO, 1995).…”
Section: Introductionunclassified
“…Choi e Zhu (2015) identificaram que a resposta visual e as sensações visuais poderiam ser avaliadas a partir das mudanças no tamanho da pupila, devido a que o sistema visual responde de forma automática aos estímulos do ambiente, já que é controlado pelo sistema nervoso parassimpático (CHOI; ZHU, 2015). Recentemente, Hamedani et al (2020) concluíram que, sob condições de maior desconforto visual as respostas das medidas fisiológicas testadas (fixação visual, piscadas e diâmetro da pupila) foram significativamente diferentes às respostas visuais sob condições menos desconfortáveis.…”
Section: Introductionunclassified